Z zelenimi knjižnicami do zelene prihodnosti - Kebe, Naja (Knjižnica, 2019)
A Green Library is a library that, with its operation, location selection, use of green technologies and exploitation of natural resources, works economically and minimizes interference with the environment. Examples of green library best practices can be found all over the world. The aim is to familiarize Slovenian librarians with this topic, bring them closer to the green library concept and promote the importance of environmentally friendly libraries. One of the goals is also to define the following concepts: green, green libraries, sustainability and sustainable development. The article presents the beginnings and development of green libraries in the world and identifies the situation and possibilities for further development of green libraries in Slovenia. The first part defines the concepts of green, green libraries, sustainability and sustainable development and describes the beginnings of green libraries. Furthermore, the focus is on the important national initiatives of Croatia and the United States of America. Crucial international initiatives are also presented in the article. In the second part, the situation in Slovenia is represented in connection with sustainable development. The I feel Slovenia brand, the Green Network and the examples of the Slovenian green libraries - Franc Ksaver Meško Ormož Library and Šentvid Library, a unit of Ljubljana City Library are mentioned. By reviewing the web pages of the Slovenian public libraries (their published work programmes, the business reports or the strategic plans), we have determined the green orientation of the Slovenian public libraries. The Werner checklist was used for the criterion.
Keywords: ekologija; splošne knjižnice; trajnostni razvoj; varstvo okolja; zelene knjižnice